2019
DOI: 10.1002/anie.201903303
|View full text |Cite
|
Sign up to set email alerts
|

Design of Photostable, Activatable Near‐Infrared Photoacoustic Probes Using Tautomeric Benziphthalocyanine as a Platform

Abstract: Near‐infrared (NIR) imaging techniques have attracted significant attention for biological and medicinal applications due to the ability of NIR to penetrate deeply into tissues. However, there are very few stable, activatable molecular probes that can utilize NIR light in the wavelength range beyond 800 nm. Herein, we report a new activatable NIR system for photoacoustic imaging based on tautomeric benziphthalocyanines (BPcs). We found that the existence of a free hydroxyl group is crucial for NIR absorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Toriumi et al reported tautomeric benziphthalocyanines, by introducing free hydroxyl group with esterase- or H 2 O 2 -labile markers, for activatable PA detection of esterase or H 2 O 2 . 55 Xie et al designed Pc-based semiconducting macromolecule, which first underwent ROS-induced cleavage process of PEG and then subsequently the residual Pcs self-assembled into large nanoparticles, showing enhanced PA signal [ Fig. 5(b) ] in the presence of ROS.…”
Section: Biomedical Applications Of P C /N Csmentioning
confidence: 99%
“…Toriumi et al reported tautomeric benziphthalocyanines, by introducing free hydroxyl group with esterase- or H 2 O 2 -labile markers, for activatable PA detection of esterase or H 2 O 2 . 55 Xie et al designed Pc-based semiconducting macromolecule, which first underwent ROS-induced cleavage process of PEG and then subsequently the residual Pcs self-assembled into large nanoparticles, showing enhanced PA signal [ Fig. 5(b) ] in the presence of ROS.…”
Section: Biomedical Applications Of P C /N Csmentioning
confidence: 99%
“…Uchiyama and coworkers approached the ROS detection with a novel design inspired by Pc, namely benziphthalocyanine (BPc, 14c), incorporating a phenol in the Pc macrocycle (Figure 11) [102]. The BPc exhibited a quinoid-phenolic equilibrium and a high photostability, as Pcs, but weak NIR absorption 870 nm (ε = 1.64 × 10 3 M −1 cm −1 ) and no fluorescence emission.…”
Section: Pa Applications Of Phthalocyanine (Pc) and Napthalocyanine (Nc)mentioning
confidence: 99%
“…Naoyuki et al. reported a novel activatable system of the PA probe which was constructed based on benziphthalocyanines (BPcs) [43] . They found BPc with a free hydroxy group existed as a tautomeric mixture of a weakly phenol form ( 8 c , 6π‐conjugation) and a strongly quinoidal form (18π‐conjugation) in solution.…”
Section: General Design Strategies Of Pa Probesmentioning
confidence: 99%